THEME-RHEME ORGANIZATION OF LEARNERS’ TEXTS - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2010)
Writing seems to be the most difficult subject for many students. In order to be able to write effectively, the students should have sufficient knowledge of what to write and of how to organize the language. To produce good writing, it is necessary for the students to know how to organize Theme and Rheme in their writing. The interaction of Theme and Rheme governs how the information in a text develops. This research tries to investigate the texts written by the English learners. The purpose is to know which thematic development pattern mostly applied in their texts. The data of this research are 15 learners’ texts. The steps in analyzing the data are first: taking texts written by the students, second: reading the texts, third: identifying the theme and rheme of every clause of the students’ texts, fourth: describing the thematic development of the students’ texts, fifth: drawing the thematic development of the students’ texts. The results of the research show that 7 (47%) students mostly apply theme reiteration or constant theme pattern, 5 (33%) students mostly apply linear or zig-zag theme pattern, and 3 (20%) mostly apply split or multiple theme pattern. Constant theme pattern is mostly preferred by the students because this pattern is the easiest one. Multiple theme pattern is considered the most difficult for the students because they need to create new themes by taking up from the rhemes. Based on the findings, some suggestions can be put forward as follows: The students should be exposed with paragraphs having multiple theme pattern in order that they are familiar with these pattern. After the exposure, they should practice writing paragraphs with this pattern.   Key Words:   Theme, Rheme, Thematic-development pattern, Theme reiteration / constant theme pattern, Zig zag/  linear theme pattern, Multiple theme / split rheme pattern.